Administration of Bone Marrow-Derived Mononuclear Cells Contributed to the Reduction of Hypoxic-Ischemic Brain Injury in Neonatal Rats - Sato, Yoshiaki; Ueda, Kazuto; Kondo, Taiki; Hattori, Tetsuo; Mikrogeorgiou, Alkisti; Sugiyama, Yuichiro; Suzuki, Toshihiko; Yamamoto, Michiro; Hirata, Hitoshi; Hirakawa, Akihiro; Nakanishi, Keiko; Tsuji, Masahiro; et al. (Frontiers in Neurology, 2018)
Background/Objective: Perinatal hypoxic-ischemia (HI) causes neonatal death and permanent neurological deficits. Cell therapy using various cell sources has been recently identified as a novel therapy for perinatal HI. Among the available types of cell sources, bone marrow-derived mononuclear cells (BMMNCs) have unique features for clinical application. For example, stem cells can be collected after admission, thus enabling us to perform autologous transplantation. This study aimed to investigate whether the administration of BMMNCs ameliorated HI brain injury in a neonatal rat model. Methods: Seven-day-old rats underwent left carotid artery ligation and were exposed to 8% oxygen for 60 min. BMMNCs were collected from the femurs and tibias of juvenile rats using the Ficoll–Hypaque technique and injected intravenously 24 h after the insult (1 × 105 cells). Active caspase-3, as an apoptosis marker, and ED1, as an activated microglia/macrophage marker, were evaluated immunohistochemically 48 h after the insult (vehicle, n = 9; BMMNC, n = 10). Behavioral assessments using the rotarod treadmill, gait analysis, and active avoidance tests were initiated 3 weeks after the insult (sham, n = 9, vehicle, n = 8; BMMNC, n = 8). After these behavioral tests (6 weeks after the insult), we evaluated the volumes of their hippocampi, cortices, thalami, striata, and globus pallidus. Results: The mean cell densities of the sum of four parts that were positive for active caspase-3 significantly decreased in the BMMNC group (p < 0.05), whereas in the hippocampi, cortices, thalami, and striata cell densities decreased by 42, 60, 56, and 47%, respectively, although statistical significance was not attained. The number of ED1 positive cells for the sum of the four parts also significantly decreased in the BMMNC group compared to the vehicle group (p < 0.05), whereas in each of the four parts the decrease was 35, 39, 47, and 36%, respectively, although statistical significance was not attained. In gait analysis, the BMMNC normalized the contact area of the affected hind paw widened by HI. The volumes of the affected striata and globus pallidus were significantly larger in the BMMNC group than in the control group. Conclusion: These results indicated that the injection of BMMNCs ameliorated HI brain injury in a neonatal rat model.